Seasonal and nutritional changes in the short form of the leptin receptor expression and VEGF system in the choroid plexus, arcuate nucleus, and anterior pituitary in MTS-leptin and resistin-treated sheep - Zieba, Dorota Anna; Biernat, Weronika; Szczesna, Malgorzata; Kirsz, Katarzyna; Misztal, Tomasz (Frontiers in Neuroscience, 2023)
The short form of the leptin receptor (LeptRa) plays a key role in the transport of leptin to the central nervous system (CNS). Here, MTS-leptin and recombinant ovine (ro) leptin-mediated expression of LeptRa and VEGFA and VEGFR2 concentration in selected hypothalamic nuclei, choroid plexus (ChP), and anterior pituitary (AP) were analyzed considering the photoperiod and acute-fasting (experiment 1), and nutritional status (experiment 2) of ewes. In experiment 1, sixty sheep were fed normally or fasted for 72 hr and received one injection of saline or, MTS-leptin, or roleptin one hour prior to euthanasia. LeptRa mRNA transcript levels and VEGF system'ssystem protein concentrations were detected in the ARC, ChP predominantly in the SD, and for AP for the LD without detection of LeptRa in the POA and VMH/DMH. In experiment 2, an altered diet for 5 months created lean or fat sheep. Twenty sheep were divided into four groups: the lean and fat groups were given saline, while the lean-R and fat-R groups received resistin one hour prior to euthanasia. Changes in adiposity influenced the lowering effect of resistin on the expression of LeptRa and VEGF system protein concentrations. Overall, both photoperiodic and nutritional signalsThis is a provisional file, not the final typeset article influence the effects of MTS-leptin/roleptin and resistin-mediated leptin transport to the CNS via LeptRa. Resistin seems to be another adipokinadipokine involved in the adaptive/pathological phenomenon of leptin resistance in sheep.Trial Registration N/A 1 Z komentarzem [pdhDZP1]: Reviewer#1 1. Unfortunately, the manuscript is very long, with many typos and sentences that seem to have been cut but not finished making the story unclear.Z komentarzem [pdhDZP2]: Reviewer#1 1. Unfortunately, the manuscript is very long, with many typos and sentences that seem to have been cut but not finished making the story unclear.Z komentarzem [pdhDZP3]: Reviewer#2 1. Although the study shows an association between Resistin and leptin resistance, there is no compelling evidence or story to support this conclusion.